(untitled) (Konferensiyalar | Conferences, 2024)
The article looks at the poetics of our nation’s favorite poet, Hero of Uzbekistan Erkin Vahidov. Our child is a witness that the realization of people’s dreams and hopes is skillfully reflected in the work of the poet.